No Ethnic Differences in the Association of Glycated Hemoglobin With Retinopathy: The National Health and Nutrition Examination Survey 2005–2008 - Bower, Julie K. (American Diabetes Association, 2013)
OBJECTIVE: Current recommendations for the use of hemoglobin A(1c) (HbA(1c)) in diabetes screening and diagnosis aim to identify those at greatest risk for diabetic microvascular complications. However, there is current controversy regarding the clinical implications of ethnic differences in HbA(1c) values. The objective of this study was to determine whether the association between HbA(1c) and retinopathy differs by ethnic group in a representative sample of U.S. adults. RESEARCH DESIGN AND METHODS: The study was a cross-sectional analysis of 2,945 non-Hispanic white, 1,046 non-Hispanic black, and 1,231 Hispanic American participants aged ≥40 years from the 2005–2008 National Health and Nutrition Examination Survey. RESULTS: Among nondiabetic adults, the mean HbA(1c) was 5.5% in non-Hispanic whites, 5.7% in non-Hispanic blacks, and 5.6% in Hispanic Americans. Among those with diagnosed diabetes, mean HbA(1c) was 6.9% in non-Hispanic whites, 7.5% in non-Hispanic Blacks, and 7.7% in Hispanic Americans. Overall, non-Hispanic blacks had the highest prevalence of retinopathy. In multivariable logistic models, HbA(1c) clinical categories were strongly associated with prevalent retinopathy. However, the magnitude of the association did not differ by ethnic group (all P values for interaction ≥ 0.7). Similar results were observed with HbA(1c) modeled continuously (per one percentage point) and stratified by diabetes status (all P for interactions > 0.3). CONCLUSIONS: We observed no ethnic differences in the association of HbA(1c) with retinopathy. These data do not support ethnic-specific cut points for HbA(1c) for diagnosis or screening of diabetes mellitus.